Terahertz thermometry system to measure temperature in the thickness of a solid polymer*. Issue 1 (2nd January 2018) - Poulin, Cyndie; Triki, Meriam; Bousmaki, Karim; Duhant, Alexandre; Louche, Hervé; Wattrisse, Bertrand
Abstract: This paper deals with thermal attenuation of a transmitted THz signal (165 GHz) across a POM polymer sample subjected to a thermal gradient in the thickness direction. The paper describes the experimental setup, including a THz sensor, a system to impose thermal loading and an infrared camera used to measure temperature variations at the surface. The thermal dependence of the transmitted THz signal through the sample was studied along a spatial profile. A simple polynomial model, validated through finite element analysis and thermal imaging measurement, was used to estimate temperature variations in the thickness direction. The correspondence between the 2D transmitted THz signal and the 3D temperature distribution allowed us to estimate the thermal sensitivity of the absorption coefficient in the THz range. This study showed that the THz sensor was sensitive enough to measure THz signal variations due to small temperature variations. The mean temperature may be determined along the thickness direction once the thermodependence of the transmission and reflection coefficients are known.